UPAYA MENINGKATKAN LITERASI SAINS PADA ANAK USIA DINI BERBANTUAN MEDIA PEMBELAJARAN KOMIK MELALUI METODE BERCERITA: Classroom Action Research On Grouf B Children of PGRI Rancakalong Kindergen, Rancakalong District, Sumedang Regency, Academic Year 2023/2024 - Antisa, Nanan; Erna Roostin; Mayasari (JESA-Jurnal Edukasi Sebelas April, 2024)
This research is motivated by the problem of low children's scientific literacy which is caused by a lack of supporting materials and teacher creativity in creating interesting learning media for children. Especially in creating and implementing comic learning media through the storytelling method to increase children's scientific literacy. This research aims to increase scientific literacy. This research uses Classroom Action Research (PTK) with the Kemmis and Taggart model. The results from the field show that the average score increase between the initial conditions and cycle I was 0.7 and the percentage increase was 0% in the Not Yet Developed (BB) category. Then the average increase between cycle I and cycle II was 1.1 with a difference in percentage increase of 40% in the Starting to Develop (MB) category. Furthermore, the increase between cycle II and cycle III was 0.4 in the Not Yet Developed (MB) category and a percentage increase of 60% in the Developing According to Expectations (BSH) category. Thus, comic learning media can improve scientific literacy skills. The benefit of this research is to increase students' insight into increasing the scientific literacy of early childhood with the help of comic learning media through the storytelling method.